Problems in learning movement skills among students in higher education - Mazlan, Adjah Naqkiah (IEEE, 2014)
Computer Based Instruction is no longer uncommon in the education arena in Malaysia. This instructional approach has been applied in the process of teaching and learning for many subjects, but little was applied to sports subject. The purpose of this study was to investigate the effects of a multimedia sports courseware in teaching movement skills, which will be developed based on the Simpson's Psychomotor Domain Taxonomy. Integrated with a video analysis technology and simulation, the courseware would be developed for all sport subjects in the sports science syllabus. This paper highlights the analysis phase of the study, which investigated students' problems in learning movement skills. In particular, the problems were divided into four types of construct (teaching strategy, learning materials, individual differences, external and internal factors). This paper also seeks to identify the dominant construct that might optimize the learning outcomes. Overall, 83 undergraduate students? majoring in sports science in one Malaysian university? were involved. The instruments used were questionnaire supported by some interviews. Quantitative data were analyzed using the SPSS 16 while qualitative data were analyzed through content analysis. The results from this initial study will be used to develop the courseware and facilitate the discussion on how it will be adopted in the process of preparing materials for the learning of movement skills. Additionally, this courseware could also promote students to a more advanced learning process that can trigger positive effects in their movement skills learning. In fact, it may also discover a young sports talent.